99Tcm-MDP Imaging of Osteopetrosis: Case Report. Issue 22 (June 2015) - Zheng, Li-Chun; OuYang, Xiang-Liu; Liu, Gui-Chao; Zhang, Wen-Jun; Zhang, Xiao-Ming
Abstract : Abstract: Osteopetrosis, also known as marble bone disease, is a clinically rare genetic disease, which represents a heterogeneous group of rare, inherited bone dysplasias that share the hallmark of abnormally increased bone density caused by osteoclast dysfunction. Hereby, the authors describe a case of osteopetrosis that showed increased diffuse radioactive uptake on whole body bone 99 Tc m -methylene diphosphonate imaging in a 56-year-old man, which increased universal radioactive uptake on craniofacial bone imaging, and enlargement of the limb long bone near the joints with evenly symmetrical enriched distribution of radioactivity. Osteopetrosis was made which based on these features and characteristics shown on 99Tcm-MDP imaging. Skeletal scintigraphy with 99 Tc m -methylene diphosphonate imaging is helpful to the diagnosis of osteopetrosis. There is a characteristic of osteopetrosis different from other bone metabolic diseases.